Records and palaeoenvironmental conditions of Early Miocene scleractinian corals from the Firat formation (Diyarbakir, Turkey) - Ekin, Ihsan; Tsaparas, Nikolaos (Masson Editeur, 2023)
Miocene scleractinian corals were documented for the first time in the Firat Formation of Sarica village, Egil district of Diyarbakir, SE Turkey. The fauna consists of four hermatypic species belonging to three families: Diploastrea taurinensis (d'Achiardi, 1868), Tarbellastraea reussiana (Milne-Edwards and Haime, 1850), Echinopora gemmacea (Lamarck, 1816) and Montastraea pelouaensis (Chevalier, 1954). The morphospecies described here are typical of the early Miocene (Aquitanian-Burdigalian) and show that the Firat Formation coral community was composed of shallow and subtropical reefs of Mediterranean Tethys palaeobiogeographical affinity. The examined species are reef components found in tropical and subtropical oceans, as are the majority of zooxanthellae. The species were upper photic zone related, had massive colonial growth morphology, and lived in a shallow tropical-subtropical marine palaeoenvironment at a depth of up to 50 m. They grew on hard ground, clean water, and normal salinity and required a minimum seawater temperature of 18 & DEG;C; however, they were most abundant at water temperatures ranging from 22 to 26 & DEG;C in high-moderate water energy. Consequently, this fossil assemblage will not only improve our knowledge of scleractinian coral diversity and morphological variation in SE Turkey but will also provide an important background for future studies of coral taxonomy, diversity and biogeography of the region. & COPY; 2023 Elsevier Masson SAS. All rights reserved.
Keywords: Mediterranean Tethys; Coral fossils; Aquitanian-Burdigalian; Palaeoenvironment; Firat Formation